The Significance of Teaching English literature in Schools in Iraq: Pentingnya Pengajaran Sastra Inggris di Sekolah-sekolah di Irak - Waham, Jihad Jaafar (Pedagogia : Jurnal Pendidikan, 2024)
The teaching of English literature in schools in Iraq has been a topic of debate for a long time. While some believe that teaching English literature is not important, others argue that it is crucial for the development of students' language skills, critical thinking abilities, and cultural awareness. This article presents an analysis of the importance of teaching English literature in schools in Iraq, highlighting the benefits that students can derive from the study of literary works in English. The article also discusses the challenges that teachers face in teaching English literature in Iraq and suggests possible solutions to address these challenges. English literature is a valuable field of study that plays an important role in the development of language and communication skills. Despite its significance, English literature is often overlooked in the Iraqi education system. This article aims to highlight the importance of teaching English literature in schools in Iraq, and the benefits that it can offer students. The article presents a problem statement, objectives, findings, and a conclusion based on a thorough analysis of relevant literature and studies.